2007
DOI: 10.1100/tsw.2007.239
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Burns in the Bedouin Population in Southern Israel

Abstract: Burn trauma is an important public health concern, with increased risk for burns in children. A cross-sectional study was performed to describe the epidemiological characteristics and risk factors for burns in hospitalized Bedouin children in Soroka University Medical Center during the years 2001–2002. In a population of 558 hospitalized burn-injured patients, 282 Bedouin children were identified. Two hundred and sixty five patients (94.0%) had burns involving less than 20% of the body surface area. Cause of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
2
32
0
3
Order By: Relevance
“…Since 88 % of the respondents reported eating common-plate meals on the recall day, we can confirm that common-plate eating is a widespread and enduring practice among Negev Bedouin adults and that an appropriate dietary assessment instrument for common-plate eating is needed. In addition, this population has undergone a major transition from semi-nomadic pastoralists and agriculturalists to sedentarized/urbanized wage labourers, and the transition has been accompanied by dramatically rising rates of chronic diseases (7)(8)(9)(10)13,14) . It is reasonable to assume that life changes, including dietary changes, have contributed to increases in chronic disease rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 88 % of the respondents reported eating common-plate meals on the recall day, we can confirm that common-plate eating is a widespread and enduring practice among Negev Bedouin adults and that an appropriate dietary assessment instrument for common-plate eating is needed. In addition, this population has undergone a major transition from semi-nomadic pastoralists and agriculturalists to sedentarized/urbanized wage labourers, and the transition has been accompanied by dramatically rising rates of chronic diseases (7)(8)(9)(10)13,14) . It is reasonable to assume that life changes, including dietary changes, have contributed to increases in chronic disease rates.…”
Section: Discussionmentioning
confidence: 99%
“…During recent decades, chronic disease rates among the Bedouin have been on the increase (7)(8)(9)(10) , as they have in many of the populations that practise common-plate eating (11,12) . Thus, the development of appropriate dietary assessment instruments that are practical for use in large-scale dietary surveillance has become increasingly important.…”
mentioning
confidence: 99%
“…This finding is consistent with a study conducted in Israel. 58 This variation of TBSA burnt percent is probably due to variations in distribution of the mechanism of burn injury. As well as severity and amount of causative agents indicated to produce variation of TBSA burnt percent.…”
Section: Tbsa Burntmentioning
confidence: 99%
“…The mean BMI was 30 in females and 29 in males Cohen et al [41] 2005 Population of the Negev area The prevalence of diabetes was 5.1% in Bedouins, 3.7% in non-Bedouins, 5.5% in urban Bedouins, 3.9% in rural Bedouins. Diabetes was well controlled in 29.3% of the Bedouins and 46.7% of the non-Bedouins Tamir et al [43] 2007 28449 Bedouins, 14012 Jews, older than 20…”
Section: Date Subjects Study Resultsmentioning
confidence: 96%
“…diabetes patients [41] . A study at the largest urban Bedouin outpatient clinic in 2002 revealed that the prevalence of diabetes was 7.3% among men and 9.9% among women.…”
Section: Nutrition and Obesity Among Bedouins In The Negevmentioning
confidence: 99%